If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8a + 1) + -2a = 124 Reorder the terms: (1 + 8a) + -2a = 124 Remove parenthesis around (1 + 8a) 1 + 8a + -2a = 124 Combine like terms: 8a + -2a = 6a 1 + 6a = 124 Solving 1 + 6a = 124 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6a = 124 + -1 Combine like terms: 1 + -1 = 0 0 + 6a = 124 + -1 6a = 124 + -1 Combine like terms: 124 + -1 = 123 6a = 123 Divide each side by '6'. a = 20.5 Simplifying a = 20.5
| 2x-6+7x=-87 | | 6x+10=15+x | | 40x+3y=280 | | 0.66(6x+3)=4x+2 | | -7+x=-5x-31 | | 2x+3(3x-1)=41 | | 40+14y=-2-8y-6 | | 20x+10y=100 | | -41=7x-3x+7 | | 9x-5=-3x+19 | | 4(3-2x)=2(2x+6) | | 16z^2+16z+3=0 | | -7+7x-3x=-39 | | 9x^2+144=0 | | -8(y-10)-15=-2y-(y-5) | | 10y-16=5(2y+4) | | 5x-8+3x=72 | | 2y-5y+7=13 | | 2x+8y=34 | | x(x^2-3x-4)= | | .25+.14x=.17+.17x | | 3(2z-3)=5(z+3) | | 4+2x-5x=-2 | | -6y+3x=-1 | | 3b(6b^2-5b-7)= | | 4(2x+5)=6(5x-4) | | 0.75t-0.83=0.66t | | 6=x+x+6 | | 2x*25=30x | | 2(y+2)=3y-4 | | 2w+5x-11y+6w=9x+6y | | 2w+5x-11y+6w=9x-6y |